HEALTH SERVICES CONSUMPTION AND BARRIERS IN THE HEALTH CARE OF PERSONS OF ROMA ORIGIN IN BULGARIA - Mariela Kambouraova; Borislava Ivanova; Radoslava Tihomirova; Eleonora Mineva-Dimitrova; Ana Ivanova; Dimitar Dimitrov; Zornitsa Yordanova; Emil Simeonov; Tsevelina Vitkova (Peytchinski Publishing, 2024)
Introduction: Persons of Roma origin often face serious inequities concerning their state of health and their access to good quality health services. The purpose of the study is to analyze the health services consumption and barriers in the health care of persons of Roma origin in Bulgaria. Material/Methods: The cross-sectional study was conducted, and a semi-structured face to face interview were applied in 2018. Adult citizens of Roma origin were covered as follows: residents of Knezha - a total of 59 people and households from the towns of Kneja and Kotel - 18 families (50 persons). The cities are representative of settlements of medium size with separate neighborhoods of Roma origin. Data processing was performed by SPSS v.24. Results: Over two-thirds of the covered persons of Roma origin do not have health insurance. Due to a lack of health insurance, 14% of the households were reported a refusal to provide health care by general practitioners (GPs) and specialists in out-hospital care. 82.1% of Roma women have never had a mammography, and 71.4% a smear test. 83.3% of the households required direct payment for the provision of health services, which corresponds to the high share of informal payments in health care in Bulgaria (34 % in 2023), but among the Roma population, this share is significantly higher. Conclusion: The Roma population in Bulgaria is characterized by an unfavourable health profile, and the health services provided to the persons of Roma origin are inadequate to their needs.